ATURAN DI PERSIMPANGAN JALAN : Perdebatan Rancangan Undang-Undang (RUU) Perkawinan 1973-1994 - Aprianto, Tri Chandra (Historia, 2018)
This paper explains the presence of a political product that regulates marital problems in Indonesia. In the process there is a political tension between those who approve it and who don't. A political compromise then ran before the Act was introduced in 1974. This paper highlights three main points: 1. the New Order's political interests; 2. the Islamic groups resistance; and 3. the women groups reaction. Keywords: Regulates Martial; political conflict; Islamic groups; women’s groups